Influence of Perivascular Adipose Tissue on Central Arterial Mechanics and Hemodynamics: A Parametric Fluid Structure Interaction Analysis - Huda, Fatma Tahsin (East Carolina University)
This study aims to evaluate the biomechanical influence of perivascular adipose tissue (PVAT) on arterial wall mechanics and hemodynamics, which are key regulators in cardiovascular disease progression. Fluid-structure interaction (FSI) models of blood flow in three idealized central arteries surrounded by PVAT of different mechanical properties and thicknesses were solved using the open-source finite element software, FEBio. For FSI analysis, normal, aged, and fibulin-5 deficient (early aging symptoms) suprarenal abdominal aorta (SAA), infrarenal abdominal aorta (IAA), and common carotid artery (CCA) of mice are used as model vessels. Different in-vivo configurations of blood vessels, such as pulsatile flow, non-Newtonian blood flow characteristics, and anisotropic properties of the arterial wall, are included for realistic outcomes. The results of the computational model show that the mechanical properties of adipose tissue significantly influence maximum tensile stress, wall shear stress, and arterial expansion. The comparison between simulation results shows that the maximum tensile stress on the arterial wall and expansion of the artery in response to hemodynamic load decreases with an increasing modulus of PVAT. In contrast, the wall shear stress of the artery increases with an increasing modulus of PVAT. The results of the effect of varying of PVAT thickness show a minor influence on the arterial wall expansion and wall shear stress. While these FEM models were designed for parametric analysis of PVAT influence on vessel mechanics, they were also used to evaluate the difference in arterial expansion for Newtonian and non-Newtonian blood flow characteristics. The findings of this study highlight the importance of including adipose tissue in evaluating arterial wall mechanics and hemodynamic parameters in cardiovascular disease research.
Keywords: Adipose tissues; Hemodynamics; Heart--Diseases